Artists/Computers/Art. - Canada House Cultural Centre Gallery, London; Centre Culturel Canadien, Paris (London : Canadian High Commission, 1982)
Crabtree, Chris ; Goldberg, Theo ; Hushlak, Gerald ; Mazlack, Lawrence J. ; Palumbo, Jacques ; Truax, Barry ; White, Norman ; TV Ontario
Artists/Computers/Art, Canada House Cultural Centre Gallery, London, 24 March - 20 April 1982 ; Centre Culturel Canadien, Paris, 3-22 juin 1982
boek